Malformações em cinco espécies de anuros em florestas urbanas do município do Rio de Janeiro, Sudeste do Brasil - Flor Baroni, Thamiris; Canedo, Clarissa; Pombal Jr, José P. (Herpetologia Brasileira, 2026)
In recent years, there has been a significant increase in studies focused on malformations and morphological anomalies in anuran species. This is primarily a consequence of growing concern on the observed decline of natural populations of anurans, and the widespread reports of malformed individuals within altered environments. As a result, most of the studies have been conducted in areas where the environmental alterations are noteworthy, such as areas with potential pesticide contamination. In areas with less perceptible environmental impacts, the number of studies remains limited. Most of the available data focus on the external anatomy of malformed specimens, while very few describe the osteology of these specimens. Although such studies increasingly deal with Neotropical species, most studies focus on the Holarctic region. It is noteworthy that most of these articles describe malformations for a limited sample, with population-based or experimental approaches being relatively rare. We conducted a large-scale analysis of individuals in five anuran species within the Parque Nacional da Tijuca, Rio de Janeiro, southeastern Brazil. We examined 622 specimens for external malformation using a stereoscopic microscope and radiographed all the specimens for osteological malformation. The malformations were quantified and comprehensively described. Among the 622 specimens analyzed, we identified 20 malformed individuals, encompassing eight Hylodes nasus, six Aplastodiscus albofrenatus, three Adenomera marmorata, two Brachycephalus ephippium, and one Ischnocnema guentheri. The low occurrence of malformations corroborates the hypothesis that they are rare in areas with little environmental impact. Furthermore, we described for the first time two new categories of malformations, namely ‘Curved Phalanx’ and ‘Incomplete Pelvic Girdle’.